Workplace's Development of Activities and Action Plans to Prevent Violence From Clients in High-Risk Sectors. Issue 1 (January 2023) - Karlsen, Iben Louise; Andersen, Dorte Raaby; Jaspers, Sofie Østergaard; Sønderbo Andersen, Lars Peter; Aust, Birgit
Introduction: Interventions trying to prevent violence from clients towards employees tend to show limited effect on the risk or the frequencies of violent episodes, possibly due to a too-narrow focus on only one or a few preventive strategies. This study aimed to show what employees and line managers identify as key intervention areas for preventing violence and threats. Methods: The study is based on data collected during a participatory intervention study aiming to improve violence prevention in Danish psychiatric units and prison and detention centers. In the intervention study, employees and line managers from 13 work units developed 293 suggestions and 92 action plans to prevent workplace violence. Through qualitative thematic analysis of the suggestions and action plans, we identified the main categories that work units viewed as important and realistic to work with to improve violence prevention. Results: We identified 12 topics of violence prevention that work units considered relevant. Action plan topics used by more than half of the work units included: specific approaches to violence prevention (e.g., de-escalating techniques), communication between employees to transfer knowledge between shifts, and introduction to new employees and temporary workers. Topics used by three to five work units were: interdisciplinary corporation, communication and relational work, uniform approaches, organization of work, and staffing. Topics used rarely were: definition of violence and threats, policy and guidelines, support from colleagues and management, and engagement in violence prevention. For nine of the 12 topics, action plans were developed in both high-risk sectors. Conclusions: The violence prevention action plans developed by work units from two high-risk sectors indicate that workplaces estimate the prevention of client-induced workplace violence to require activities on many levels and cannot be solved by a single focused approach. This variety of preventive activities needs to be considered when designing violence prevention interventions.